2016
DOI: 10.1016/j.neuron.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuits Underlying Visually Evoked Escapes in Larval Zebrafish

Abstract: SUMMARY Escape behaviors deliver organisms away from imminent catastrophe. Here, we characterize behavioral responses of freely swimming larval zebrafish to looming visual stimuli simulating predators. We report that the visual system alone can recruit lateralized, rapid escape motor programs, similar to those elicited by mechanosensory modalities. Two-photon calcium imaging of retino-recipient midbrain regions isolated the optic tectum as an important center processing looming stimuli, with ensemble activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
363
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(400 citation statements)
references
References 70 publications
35
363
2
Order By: Relevance
“…The optical parameters that have been most commonly associated with the response time are: (1) angular size, e.g. in locusts (Fotowat and Gabbiani, 2007), flies (Card and Dickinson, 2008) or fish (Dunn et al, 2016); (2) angular increment, e.g. in crayfish (Glantz, 1974); and (3) a combination of angular size and velocity, which allows an estimation of the time to collision, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical parameters that have been most commonly associated with the response time are: (1) angular size, e.g. in locusts (Fotowat and Gabbiani, 2007), flies (Card and Dickinson, 2008) or fish (Dunn et al, 2016); (2) angular increment, e.g. in crayfish (Glantz, 1974); and (3) a combination of angular size and velocity, which allows an estimation of the time to collision, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on the response of a single morphologically wellidentified type of neuron, such as the LGMD of the locust (e.g. , or on population responses of neurons, such as those recently described in the optic tectum of the zebrafish (Dunn et al, 2016). In both examples, the neural response encodes the dynamic of the stimulus expansion, and the activity reached at a fixed angular size was associated with the stimulus threshold of the corresponding avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…While detailed kinematic information can be obtained from 2D imaging, such as speed, latency, direction and frequency of swimming movements, a restriction in vertical range can be a confound in locomotor assays (Zhu and Weng, 2007) and leaves open the question of whether vertical swimming would occur as part of the 'natural' behavior. Recordings of neural activity have been used in conjunction with analyses of swimming movements to study escape circuits in zebrafish, including recent advances made by measuring the lateral direction of escape tail movements during optical calcium imaging of neurons in the brain (Dunn et al, 2016;Temizer et al, 2015). These and other neural recording methods have elucidated mechanisms of lateral movement control in zebrafish (Kohashi and Oda, 2008;Gabriel et al, 2009;Knogler and Drapeau, 2014), but the need to partially or fully immobilize the animal limits the potential to detect vertical movements.…”
Section: Introductionmentioning
confidence: 99%
“…The tectal neuropil contains these afferent axons, the dendrites of periventricular layer (PVL) neurons, and the axons of PVL interneurons. PVL neurons are morphologically diverse, including both tectal interneurons and projection neurons (Figure 1.7) Robles et al, 2011), and the tectal circuits arising from these cells are necessary for high-acuity vision, and for distinguishing between small prey items and larger visual features that may represent predators (Del Bene et al, 2010;Preuss et al, 2014;Semmelhack et al, 2014;Bianco and Engert, 2015;Temizer et al, 2015;Dunn et al, 2016). Anatomical and functional studies have suggested that visual information principally enters superficial laminae of the neuropil, and is progressively filtered before being relayed to other brain regions by the PVL projection neurons Del Bene et al, 2010;Robles et al, 2011;Gabriel et al, 2012).…”
Section: The Tectum Of Teleost Fishmentioning
confidence: 99%
“…At 6dpf, zebrafish are able to track and capture prey (Borla et al, 2002), can respond to predatory visual cues (Temizer et al, 2015;Dunn et al, 2016), perform phototaxis (Burgess et al, 2010) and can display optomotor and optokinetic responses (Roeser and Baier, 2003). Beyond visual behaviours, zebrafish have been shown to be capable of exhibiting complex social behaviours such as shoaling and aggression (Engeszer et al, 2004;Engeszer et al, 2007;Saverino and Gerlai, 2008;Dreosti et al, 2015), and are capable of responding appropriately to chemical stimuli (Speedie and Gerlai, 2008;Ogawa et al, 2014).…”
Section: Zebrafish As a Neuroanatomical Modelmentioning
confidence: 99%